2007
DOI: 10.1038/sj.bjc.6603930
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of cancer-specific NF-κB-CEA enhancer–promoter system for 5-fluorouracil prodrug gene therapy in colon cancer cell lines

Abstract: Nuclear factor-kappa B (NF-kB) is a transcription factor with high transcriptional activity in cancer cells. In this study, we developed a novel enhancer -promoter system, kB4-CEA205, in which the basal carcinoembryonic antigen (CEA) promoter sequence (CEA205) was placed downstream of the four tandem-linked NF-kB DNA-binding sites (kB4). In combination with a kB4 enhancer, the transcriptional activity of the CEA promoter was significantly enhanced (three-to eight-fold) in cancer cell lines but not in normal ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 31 publications
(42 reference statements)
1
6
0
Order By: Relevance
“…We found the highest expression among all colon cancer cells in HTC-116 cell lines (33.4%) and the lowest in T-84 cells (3.49%); whereas normal CCD18co cells revealed practically undetectable levels of CEA. These results for CEA promoter activity are similar to those described by Gou et al [ 31 ] and Dąbrowska et al [ 32 ], who also observed a greater CEA promoter activity in colon cancer cell lines than in non-tumor cancer cell lines using a luciferase assay.…”
Section: Discussionsupporting
confidence: 91%
“…We found the highest expression among all colon cancer cells in HTC-116 cell lines (33.4%) and the lowest in T-84 cells (3.49%); whereas normal CCD18co cells revealed practically undetectable levels of CEA. These results for CEA promoter activity are similar to those described by Gou et al [ 31 ] and Dąbrowska et al [ 32 ], who also observed a greater CEA promoter activity in colon cancer cell lines than in non-tumor cancer cell lines using a luciferase assay.…”
Section: Discussionsupporting
confidence: 91%
“…Few reports described the incorporation of genetic responsive elements to promoters for enhanced transcriptional regulation of therapeutic genes (Yew et al , 2001; Greco et al , 2002; Lee et al , 2002; Liu et al , 2004; Lee et al , 2006; Guo et al , 2007; Poulsen et al , 2008), but only one study attempted to combine NF-κB and HRE elements in a plasmid that conferred only a slight enhanced activity to the KDR promoter when assessed in primary murine endothelial cells (Modlich et al , 2000). Here we observed that both in a plasmid and in an adenoviral context the triple chimeric promoter increased its transcriptional activity greatly, leading to enhanced viral efficacy under hypoxia and upon TNF-α addition in human melanoma cells and fetal fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Carcinoembryonic antigen (CEA) promoter is active only in CEA-positive cells, an exclusive characteristic of vast tumor cells; the CEA promoter-controlled CD strategy confers toxic specificity for CEA-producing colorectal cancer cells while preserving activity [54]. Furthermore, by taking advantage of the knowledge that nuclear transcriptional factor NFkB is often highly transcribed in cancer cells, the addition of NF-kB enhancer to the CEA promoter significantly enhanced the efficacy of its driven CD/5-FC system in colon cancer cells [65]. In a study to select the optimal promoter to drive CD in a GDEPT strategy against gastric cancer, promoters of SEL1L, mucin-1 and KRT19 displayed the highest activity levels among several genes that are significantly highly expressed in gastric tumors [66].…”
Section: Gene-directed Enzyme Prodrug Therapymentioning
confidence: 99%